Characterization of the complete chloroplast genome sequence of Maesa hupehensis Rehd (primulaceae). Issue 6 (3rd June 2022) - Li, Yan; Yao, Xuan; Chang, Qinxiang; Zhang, Caijuan; Xia, Pengguo
Abstract: Maesa hupehensis Rehd 1916 is mainly planted in Hubei and Sichuan. In this study, we assembled and characterized the complete chloroplast genome of M. hupehensis as resources for the future study. The chloroplast genome was 157, 005 bp in length, with 37.3% GC content, composing of one large single copy (87, 628 bp) and one small single copy (18, 111 bp), separated by two inverted repeats (25, 633 bp). A total of 130 genes were predicted, including 8 rRNAs, 37 tRNAs, and 84 protein-coding genes. Phylogenetic analysis showed that M. hupehensis was closely related to Maesa montana .